(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
This article looks at the various grammatical classifications of verbs and how they impact sentence structure and meaning. The many characteristics of verbs, including as tense, aspect, mood, voice, person, number, and transitivity, are thoroughly examined. Gaining clarity in written and spoken communication requires an understanding of these areas in order to analyze sentence structure.